Bio-degradeable Bioplastics sebagai Plastik Ramah Lingkungan - Wijayanti, Kim Poppy; Dermawan, Nathanael; Faisah, Sabila Nur; Prayogi, Vincent; Judiawan, William; Nugraha, Tutun; Listyorini, Niken Taufiqurrahmi (Surya Octagon Interdisciplinary Journal of Science and Technology, 2016)
Massive uses of conventional plastics have brought negative consequences to the aspects of sustainability and environmental friendliness of human activities, due to the problems concerning the availability of its raw materials and eventual wastes. One of the solutions to face these problems is by producing and using plastics that can degrade and be derived from renewable biomasses which are now known as bio-degradeable bioplastics.  At least, there are 4 kinds of plastics that can fulfill the criteria as being bio-degradeable bioplastics, namely starch-based plastic, cellulose-based plastics, PLA (polylactic acid), and PHA (polyhydroxylalkanoates). These four kinds of plastics have different characteristics, applications, strengths, and also weaknesses. In spite of the many challenges  in the uses of  bio-degradeable bioplastics to replace conventional plastics, newest technological development and the birth of stronger public awareness towards a more sustainable and more environmentaly-friendly life style have given stronger stronger forces to increase the uses and urgency of bio-degradeable bioplastics.